Circulatory power and ventilatory power over time under goal‐oriented sequential combination therapy for pulmonary arterial hypertension. (1st April 2017) - Hirashiki, Akihiro; Adachi, Shiro; Nakano, Yoshihisa; Kamimura, Yoshihiro; Shimokata, Shigetake; Takeshita, Kyosuke; Shimizu, Atsuya; Toba, Kenji; Murohara, Toyoaki; Kondo, Takahisa
Abstract : Many therapeutic options are available for patients with pulmonary arterial hypertension (PAH). However, little is known about the effects of sequential combination therapy on exercise capacity. Here we monitored exercise capacity by cardiopulmonary exercise testing (CPX) and observed the benefit of using a peak VO2 cutoff of 15 mL/kg/min to guide combination therapy. Thirty patients newly diagnosed with PAH were treated with goal‐oriented sequential combination therapy. Endothelin receptor antagonists (ERA) were the first‐line treatment, with phosphodiesterase type 5 inhibitors (PDE‐5i) as the preferred combination partner. The patients underwent cardiac catheterization at baseline and after 12 months and CPX at baseline and after three, six, and 12 months. Circulatory power (CP) was defined as the product of peak O2 uptake and peak systolic blood pressure (SBP); ventilatory power (VP) was defined as peak SBP divided by the minute ventilation–CO2 production slope. After 12 months, ERA had been administered to 100% of the study patients and PDE‐5i to 82%. Mean CP at baseline and after three, six, and 12 months was 1807, 2063, 2248, and 2245 mmHg·min/mL/kg, respectively, and mean VP was 2.93, 3.53, 4.16, and 3.68 mmHg, respectively. CP was greater after 6 months than at baseline ( P = 0.047); VP was greater after three months than at baseline ( P = 0.019) and further improved at six months compared with three months ( P = 0.040). Therefore, repeated CPX assessment, including measurement of CP and VP, can provide useful information regarding the efficacy of goal‐oriented treatment for PAH.